Innovation platform and governance of local rice value chains in Benin: Between game of power and internal democracy? - Hinnou, L.C.; Mongbo, R.L.; Kamanda, J.; Sanyang, S. (Informa UK Limited, 2018)
In Benin, rice plays a major role in the food security of the poorest rural and urban populations. However, the rice value chains have failed to achieve their potential because of some systemic constraints. In recent years, innovation platforms (IPs) have received increasing focus as mechanisms for strengthening the interaction between the stakeholders in the rice value chains. Nevertheless, the issues of information asymmetry and power between stakeholders with often divergent interests suppress the expected effects of the implementation of IP approach. This article used thematic content analysis to assess the influence of IPs on the governance of the parboiled rice value chain. The findings reveal that local rice value chains are characterized by unequal access to resources and asymmetry of power, which generates inequalities within groups. Although their influence is less discernible, IPs have contributed to greater visibility for some emerging stakeholders and rebalanced stakeholders in terms of influence in value chains. Moreover, the perverse effects of financial and human resources management limit the impact of improvement actions in various value chains. Therefore, the development model of value chains may be oriented toward the “business idea approach” instead of the “project approach”.